Analisis Faktor-Faktor Tingkat Penggunaan E-Commerce di Setiap Provinsi Indonesia Menggunakan Analisis Faktor - Rizqi, Farhan Muhammad; Nugrahasyach, Muhammad Rafli; Wulandari, Sri Pingit (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The increase in the percentage of e-commerce use in each province in Indonesia is influenced by a number of diverse socioeconomic and digital factors. This study aims to analyze the main factors that influence the level of e-commerce use in Indonesia in 2023. The study was conducted using factor analysis of 10 variables, namely the Schooling Years Ratio (RLS), Expected Years of Schooling (HLS), Labor Force Participation Rate (TPT), Digital Literacy Index, Information and Communication Technology (ICT), the proportion of internet users, and several indicators of the Digital Society Index (IMD) such as digital infrastructure and ecosystem, digital skills, empowerment, and technology-based employment opportunities. Factor analysis using the Principal Component Analysis (PCA) method was used to identify the dominant variables related to e-commerce adoption, especially in 34 provinces in Indonesia. The results of the analysis show that the variables that influence the percentage of e-commerce use in each province are relatively homogeneous. The assumption test on the data shows that the assumptions of multivariate normal distribution, dependent, and the suitability of the variables for factoring are met. From PCA, two main factors were identified that explained 61.237% of the data variability: The first factor is Education and Human Resource Quality, which includes the variables Average Length of Schooling, Open Unemployment Rate, Digital Literacy Index, Information and Communication Technology, and Empowerment. The second factor is Skills and Employment, which includes Digital Skills and Technology-based Jobs.